Transforaminal endoscopic discectomy - a targeted spinal surgery - Mor Japar Khan, Ed Simor Khan; Kow, Ren Yi; Siron @ Baharom, Khairul Nizam (2019)
Introduction: Open discectomy has been the gold standard of care for cases of prolapsed intervertebral disc. Tissue dissection is unavoidable in order to access the pathologic disc material. After skin incision, subcutaneous fat tissue, paraspinal muscles, ligamentum flavum, epidural fat, dura and nerve roots has to be encountered before reaching the disc material. With the transforaminal endoscopic technique, only skin and subcutaneous tissue need to be bridged before reaching the disc material. Also known as the targeted surgical technique, this technique minimized the trauma to the soft tissue. Material and Methods: We present 10 case series of prolapsed intervertebral disc which was treated with transforaminal endoscopic technique. Results : All 10 patients underwent transforaminal discectomy. All patients had satisfactory pain relief with negative SLR test post-operatively. Conclusion: We are seeing the evolution of the surgical treatment for PID/HNP, from open to microdiscectomy and now to endoscopic discectomy. In the future this might be the gold standard of treating prolapsed intervertebral disc.